Linkage between Traditional Architectural Elements in South Asia Representing Regionalism and Achieving Salutogenesis - Ishita Mouri Rahman (Recent Developments in Engineering Research Vol. 12, 2021)
In the context of the city, cultural inferences are lost, but they can be reestablished through conscious design decisions by the architect and conscious house dwellers.Connections are found by delving into the regionally developed architectural characteristics prevalent in the South Asian climate, which are critical to achieving modern green building. Sustainability is addressed in traditional architecture. Aaron Antonovsky created the term salutogenesis, which focuses on elements that support human health and well-being. This study draws the linkages between traditional architectural practices and achieving salutogenesis. Reinstalling the lost cultural inferences in architecture which have time- tested acceptability for generations, enhances the wellbeing for the dwellers in present times.